Medium-term outcome of cementless, mobile-bearing, unicompartmental knee arthroplasty - Stempin, Radosław; Stempin, Kacper; Kaczmarek, Wiesław (Annals of Translational Medicine; Vol 7, No 3 (February 01, 2019): Annals of Translational Medicine, 2019)
Background: Cemented, mobile-bearing unicondylar knee arthroplasty (UKA) yields good functional results. However, radiolucent lines (RLL) are not uncommon, even in asymptomatic patients, and it has been debated whether these “physiological” RLLs are indicative of loosening. Cementless UKA may lead to fewer RLLs compared with cemented devices. The present study was designed to document mid-term outcome with an emphasis on clinical outcomes. Methods: We included 153 knees of 150 consecutive patients in a retrospective study. All patients had received a cementless medial mobile-bearing UKA. Patients were evaluated with use of the Knee Society Score (KSS), which was obtained at baseline and at final follow-up. The WOMAC, Oxford Knee Score (OKS) and Forgotten Joint Scores (FJS-12) were administered at the final follow-up. Anteroposterior (AP) and lateral radiographs were taken at final follow-up. Results: At a mean follow-up of 5 years (range, 3–7 years), implant survival was 97.1% (95% confidence interval, 91.1–99.1%). Excellent postoperative KSS, WOMAC, OKS and FJS scores were obtained. Postoperative radiography was available for 78 knees. RLL was observed in 10.3% of the cases, but no cases with complete RLLs were seen. Conclusions: Favourable results were found for cementless, mobile-bearing UKA, with no aseptic loosening at an average follow-up of 5 years. Cementless UKA fixation may lead to a clinically “forgotten joint” and may decrease the rate of RLLs.